Cell responses to the impact of physiological doses of ultraviolet radiation and their modulation by plant polyphenols - Kostyuk, Vladimir A.; Albuhaydar, Ahmed; Potapovich, Alla I.; Korkinа Lyudmila G. (Experimental Biology and Biotechnology, 2019)
In this study it was investigated the responses of cultured human cells – keratinocytes and fibroblasts to physiological doses of ultraviolet radiation (UVR) applied with or without plant polyphenolic compounds: rutin, quercetin, taxofolin, silybin and baikalein. Experimental data obtained in this work indicate the presence of synergism in the action of physiological doses of UVR and plant polyphenolic compounds on inflammatory signaling pathways in keratinocytes and fibroblasts. It is concluded that the identified synergies can contribute to the adaptation of the skin to subsequent exposure to UVR, and thus be one of the photoprotective mechanisms of the plant polyphenolic compounds.